Identification of Surgically Curable Primary Aldosteronism by Imaging in a Large, Multiethnic International Study - Rossi, Gian Paolo; Crimì, Filippo; Rossitto, Giacomo; Amar, Laurence; Azizi, Michel; Riester, Anna; Reincke, Martin; Degenhart, Christoph; Widimsky, Jiri; Naruse, Mitsuhide; Deinum, Jaap; Schultze Kool, Leo; et al. (The Journal of clinical endocrinology and metabolism, 2021)
CONTEXT: Adrenal gland imaging is recommended by the current guidelines for the workup of primary aldosteronism (PA). However, its diagnostic performance has not been established in large, multiethnic cohorts of patients who undergo adrenal vein sampling (AVS) and adrenalectomy. OBJECTIVE: This work aims to assess the diagnostic accuracy of cross-sectional adrenal imaging. METHODS: This international multicenter study took place in tertiary referral centers. A total of 1625 PA patients seeking surgical cure were enrolled in an international study involving 19 centers in North America, Europe, Asia, and Australia. Of these, 1311 (81%) had imaging data available and 369 (23%), who received a final diagnosis of surgically cured unilateral PA, were examined. Patients underwent AVS and imaging by computed tomography and/or magnetic resonance imaging. The accuracy of detection of unilateral PA at imaging was estimated by the area under the receiver operator characteristics curve using cure (biochemical and/or full clinical success) as the reference at follow-up after unilateral adrenalectomy. RESULTS: In the cohort of 1311 patients with imaging data available, 34% and 7% of cases showed no detectable or bilateral nodules, respectively. Imaging did not detect the culprit adrenal in 28% of the surgically cured unilateral PA patients. Moreover, the clinical outcome did not differ significantly between the imaging-positive and imaging-negative patients. CONCLUSION: Cross-sectional imaging did not identify a lateralized cause of disease in around 40% of PA patients and failed to identify the culprit adrenal in more than one-fourth of patients with unilateral PA.
Keywords: dospělí; Magnetic Resonance Imaging; Europe; Asia; Female; aldosterone; Adult; výsledek terapie; ženské pohlaví; Tomography, X-Ray Computed; endocrine hypertension; primary aldosteronism; adrenalektomie; Australia; diagnosis; lidé; Evropa; Sensitivity and Specificity; nadledviny; magnetická rezonanční tomografie; vény; Veins; Treatment Outcome; senzitivita a specificita; Austrálie; kohortové studie; Adrenalectomy; Humans; Cohort Studies; retrospektivní studie; Hyperaldosteronism; North America; Male; Aldosterone; Severní Amerika; Adrenal Glands; Asie; lidé středního věku; MRI; mužské pohlaví; hyperaldosteronismus; Retrospective Studies; Middle Aged; CT; aldosteron; počítačová rentgenová tomografie